Real Estate Marketing in Jordan - Analytical qualitative research - Alzheimat, Samer Ahmed Abdullah (Arab Journal for Sciences and Research Publishing, 2016)
This study focused on real estate marketing in Jordan by studying the concepts, rules and methods of real estate marketing, and how to provide the necessary needs for the real estate consumer and focus on the most important foundations in the organization of real estate trading (buy or sell) and showed that the main factors to determine real estate marketing in Jordan may be almost similar to many countries with some specificities here or there, and the analytical qualitative method was used in this study.
Keywords: marketing; real estate; Jordan